Ion‐Pairing Assemblies Based on Pentacyano‐Substituted Cyclopentadienide as a π‐Electronic Anion. Issue 23 (27th April 2016) - Bando, Yuya; Haketa, Yohei; Sakurai, Tsuneaki; Matsuda, Wakana; Seki, Shu; Takaya, Hikaru; Maeda, Hiromitsu
Abstract: Pentacyanocyclopentadienide (PCCp − ), a stable π‐electronic anion, provided various ion‐pairing assemblies in combination with various cations. PCCp − ‐based assemblies exist as single crystals and mesophases owing to interionic interactions with π‐electronic and aliphatic cations with a variety of geometries, substituents, and electronic structures. Single‐crystal X‐ray analysis revealed that PCCp − formed cation‐dependent arrangements with contributions from charge‐by‐charge and charge‐segregated assembly modes for ion pairs with π‐electronic and aliphatic cations, respectively. Furthermore, some aliphatic cations gave dimension‐controlled organized structures with PCCp −, as observed in the mesophases, for which synchrotron XRD analysis suggested the formation of charge‐segregated modes. Noncontact evaluation of conductivity for (C12 H25 )3 MeN + ⋅ PCCp − films revealed potential hole‐transporting properties, yielding a local‐scale hole mobility of 0.4 cm 2 V −1 s −1 at semiconductor–insulator interfaces. Abstract : Taking charge : Ion‐pairing assemblies of pentacyanocyclopentadienide (PCCp − ), a stable π‐electronic anion, were constructed in combination with various cations. PCCp − ‐based assemblies exist as single crystals and mesophases owing to interionic interactions with π‐electronic and aliphatic cations with a variety of geometries, substituents, and electronic structures (see figure).